2018
DOI: 10.1128/aem.00267-18
|View full text |Cite
|
Sign up to set email alerts
|

Reconstituting the History of Cronobacter Evolution Driven by Differentiated CRISPR Activity

Abstract: strains harboring the CRISPR-Cas system are important foodborne pathogens causing serious neonatal infections. However, the specific role of the CRISPR-Cas system in bacterial evolution remains relatively unexplored. In this study, we investigated the impact of CRISPR-Cas in evolution and obtained 137 new whole-genome sequences of by next-generation sequencing technology. Among the strains examined (n=240), 90.6% (193/213) of prevalent species ,, and strains had intact CRISPR-Cas systems. Two rare species, (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 51 publications
5
15
0
Order By: Relevance
“…Results presented in this study underscore the importance of phage in the evolutionary and population dynamics of bacteria. NCPPB3778 and the CRISPR immune system are hypothesized to drive the evolution of R. toxicus , which is consistent with recent findings implicating CRISPRs in speciation of bacteria ( 52 ). Whether the low genetic diversity compromises the ability of R. toxicus to migrate from Australia and adapt to new environments is unknown.…”
Section: Discussionsupporting
confidence: 90%
“…Results presented in this study underscore the importance of phage in the evolutionary and population dynamics of bacteria. NCPPB3778 and the CRISPR immune system are hypothesized to drive the evolution of R. toxicus , which is consistent with recent findings implicating CRISPRs in speciation of bacteria ( 52 ). Whether the low genetic diversity compromises the ability of R. toxicus to migrate from Australia and adapt to new environments is unknown.…”
Section: Discussionsupporting
confidence: 90%
“…The source of infections in adults is still unidentified (Joseph and Forsythe, 2012). Some research reports indicated that the principal sources of this organism are associated with soil, water, and vegetables (Ueda, 2017; Zeng et al, 2018b). However, a clear understanding about the epidemiology and reservoirs of Cronobacter spp.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this genus has been isolated from the environment, food, and clinical sources (Ueda, 2017; Yong et al, 2018; Zeng et al, 2018a; Li et al, 2019). Further, C. sakazakii , C. malonaticus , and C. dublinensis are three prevalent species and some reports have indicated that the principal sources of these organisms might be soil, water, and vegetables (Ueda, 2017; Zeng et al, 2018b). However, the epidemiology and reservoirs of Cronobacter spp.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike subtype I-E, which was commonly detected among Cronobacter strains, subtype I-F was found to be significantly more prevalent in the plant-associated species C. dublinensis than in the human virulence-related species C. sakazakii and C. malonaticus . However, C. condimenti lacked intact CRISPR-Cas system (Zeng et al, 2017, 2018b). At the same time, significantly higher CRISPR activity was also observed in the plant-associated species C .…”
Section: Introductionmentioning
confidence: 99%